Analisis Perilaku Remaja Yang Mengkonsumsi Alkohol di Desa Picuan Lama Kecamatan Motoling Timur - Merentek, Kristania; Mautang, Theo Welly Everd; Pajung, Bertom Christian (Jurnal Lentera Sehat Indonesia, 2025)
Alcohol consumption among adolescents in Indonesia is very prevalent. The 2017 SKDI found that the prevalence of adolescents (aged 15-24 years) who consume alcoholic beverages is higher among males than females, at 15% and 1% respectively. Approximately 70% of males and 58% of females start drinking alcohol between the ages of 15 and 19. The impacts are mostly maladaptive behaviours such as fighting, promiscuity, dropping out of school, and physical injury. The research method used was quantitative correlational with a cross-sectional approach. The sample in this study used purposive sampling using the Slovin formula. The purpose of this study was to analyse the behaviour of adolescents who drink alcohol in the village of Picuan Lama, Motoling Timur sub-district. The research was conducted from August to October 2024. The results showed that males were the most numerous respondents at 88.6%, but there were also female adolescent respondents at 11.4%, with the most dominant age being 15 years old at 42.5%. Heavy drinking behaviour among adolescents was found in 48 people or 68.75%. The maladaptive/deviant attitudes of adolescent alcohol drinkers were 32.85%, and adaptive attitudes were 67.14%. The Pearson Chi-square test results showed a significance value of 0.022 < 0.05, which means that Ho is rejected and Ha is accepted, meaning that there is a relationship between the behaviour and attitudes of adolescents who drink alcohol in Picuan Lama village.